Considering the implications of climate-induced species range shifts in marine protected areas planning - Charlotte K. Whitney; William W.L. Cheung; Natalie C. Ban (Canadian Science Publishing, 2023)
Climate change is affecting the ocean, altering the biogeography of marine species. Yet marine protected area (MPA) planning still rarely incorporates projected species range shifts. We used the outputs of species distribution models fitted with biological and climate data as inputs to identify trends in occurrence for marine species in British Columbia (BC), Canada. We assessed and compared two ways of incorporating climate change projections into MPA planning. First, we overlaid 98 species with modelled distributions now and by the mid-21st century under two contrasting ("no mitigation" and "strong mitigation") climate change scenarios with existing Provincial marine parks in BC, to ask which species could overlap with protected areas in the future. Second, we completed a spatial prioritization analysis using Marxan with the projected future species ranges as inputs, to ask where priority regions exist for the 98 marine species. We found that many BC marine parks will lose species in both climate scenarios that we analyzed, and that protecting 30% of important marine species will be challenging under the "no mitigation" climate change scenario. Challenges included the coarse resolution of the data and uncertainty in projecting species range shifts.